Romidepsin Plus CHOP Versus CHOP in Patients With Previously Untreated Peripheral T-Cell Lymphoma: Results of the Ro-CHOP Phase III Study (Conducted by LYSA). Issue 3 (20th January 2022) - Bachy, Emmanuel; Camus, Vincent; Thieblemont, Catherine; Sibon, David; Casasnovas, René-Olivier; Ysebaert, Loïc; Damaj, Gandhi; Guidez, Stéphanie; Pica, Gian Matteo; Kim, Won Seog; Lim, Soon Thye; André, Marc; et al.
Abstract : PURPOSE: Romidepsin, a histone deacetylase inhibitor, has demonstrated activity in relapsed or refractory peripheral T-cell lymphoma (PTCL) as a single agent. Cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) therapy is widely used as first-line treatment of PTCL; however, it has limited efficacy. Results from a phase Ib and II study showed the feasibility of combining romidepsin with CHOP (Ro-CHOP). METHODS: This study is a randomized phase III study of Ro-CHOP versus CHOP in adult patients with previously untreated PTCL. All patients received CHOP in 3-week cycles for six cycles. Romidepsin, 12 mg/m 2, was administered intravenously over a 4-hour period on days 1 and 8 of each 3-week cycle for six cycles. The primary end point was progression-free survival (PFS) according to International Working Group 1999 criteria. RESULTS: Between January 2013 and December 2017, 421 patients were enrolled (Ro-CHOP, n = 211; CHOP, n = 210). The median PFS for Ro-CHOP versus CHOP was 12.0 months (95% CI, 9.0 to 25.8) versus 10.2 months (95% CI, 7.4 to 13.2) with a hazard ratio of 0.81 ( P = .096). In the Ro-CHOP versus CHOP arms, the median overall survival was 51.8 versus 42.9 months and the objective response rate was 63% versus 60% with complete response plus unconfirmed complete response rates of 41% versus 37% ( P > .1 in all comparisons), respectively. Grade 3 or 4 treatment-emergent adverse events occurring in ≥ 30% of patients in the Ro-CHOP arm included thrombocytopenia (50% v 10% in the Ro-CHOP v CHOP arms, respectively), neutropenia (49% v 33%), anemia (47% v 17%), and leukopenia (32% v 20%). CONCLUSION: The addition of romidepsin to CHOP did not improve PFS, response rates, nor overall survival and increased the frequency for grade ≥ 3 treatment-emergent adverse events. Ro-CHOP does not represent a significant advance in the standard of care for patients with previously untreated PTCL. Abstract :